Varicella-zoster virus infection and brivudine therapy: unexpected response in sarcoma patient - BAYOĞLU, İBRAHİM VEDAT; KÖSTEK, OSMAN (My University, 2022)
Soft tissue sarcoma is a heterogeneous disease and treatment options are limited in advanced stage settings. Brivudine is a thymidine-nucleoside analog and inhibits DNA polymerase in VZV infection. We demonstrated a case of a patient who was diagnosed with both VZV infection and advanced stage sarcoma, and unexpected anti-tumoral response after brivudine therapy.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); TIP, GENEL & DAHİLİ; ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); MEDICINE, GENERAL & INTERNAL; Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; VZV-infection; brivudine; undifferentiated pleomorphic sarcoma; anti-tumoral response; THYMIDINE KINASE 1; VZV-infection; brivudine; undifferentiated pleomorphic sarcoma; anti-tumoral response